Multicultural Islamic Education Model Based On Local Wisdom: Implementation of the Tafsir Lenyepaneun by Moh. E. Hasim in the Cicendo Bandung Community - Alam Tarlam; Eti Nurhayati; Septi Gumiandari; Ahmad Asmuni (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2026)
This study examines the implementation of an Android-based Islamic learning media grounded in Acehnese local wisdom among Generation Z students at State Islamic Higher Education Institutions (PTKI) in Aceh Province. Responding to the digital-native characteristics of Generation Z and drawing on constructivist learning theory and culturally responsive pedagogy, the research employs a qualitative case study design involving lecturers, Generation Z students, educational technologists, cultural leaders, and educational technology practitioners. Data were collected through in-depth semi-structured interviews, participant observation, and document analysis, and analyzed using thematic analysis. The findings reveal that integrating local wisdom values such as the philosophy of “Adat bak Poe Teumeureuhom, Hukom bak Syiah Kuala,” the Peusijuek tradition, and Kenduri Blang into interactive multimedia significantly enhances student engagement and contextual understanding of Islamic teachings. Among the application features, gamification elements (points, badges, and challenges) and social learning tools (discussion forums and peer feedback) demonstrated the highest impact on motivation and active participation, while content personalization strengthened individual learning pathways. The study contributes theoretically by proposing a culturally integrated digital learning model that bridges Islamic education innovation with local wisdom preservation. However, challenges remain in infrastructure readiness, human resource competence in application development, and ensuring the authenticity of digitally represented cultural content. Overall, this implementation supports effective Islamic education innovation while fostering a technologically adaptive generation rooted in Islamic values and Acehnese cultural heritage. Keywords: Educational technology, local wisdom of Aceh, Generation Z, Islamic education innovation, Android application.